2023
DOI: 10.3389/fchem.2023.1191075
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity enhancement of a Cu (II) metal organic framework-acetylene black-based electrochemical sensor for ultrasensitive detection of imatinib in clinical samples

Abstract: Imatinib (IMB), an anticancer drug, is extensively used for chemotherapy to improve the quality of life of cancer patients. The aim of therapeutic drug monitoring (TDM) is to guide and evaluate the medicinal therapy, and then optimize the clinical effect of individual dosing regimens. In this work, a highly sensitive and selective electrochemical sensor based on glassy carbon electrode (GCE) modified with acetylene black (AB) and a Cu (II) metal organic framework (CuMOF) was developed to measure the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(66 reference statements)
1
0
0
Order By: Relevance
“…[23][24][25] Regular monitoring of plasma concentrations and dosage adjustments of drugs can help to reduce side effects in patients. 26 In the present study, we found that HTR1A polymorphisms significantly affected the plasma concentrations of quetiapine versus risperidone, especially at week 6 after monotherapy. This suggests that when taking quetiapine or risperidone as a monoadministration, patients need to be regularly monitored for changes in plasma concentrations, especially in the sixth week of treatment, in order to prevent the occurrence of toxicity due to high plasma concentrations in carriers of the TT phenotype at the rs10042486 locus and the GG phenotype at the rs6295 locus, or plasma concentrations lower than the therapeutic reference concentration range occurring in carriers of the CC phenotype at the rs10042486 locus and the CC genotype at the rs6295 locus.…”
Section: Discussionsupporting
confidence: 47%
“…[23][24][25] Regular monitoring of plasma concentrations and dosage adjustments of drugs can help to reduce side effects in patients. 26 In the present study, we found that HTR1A polymorphisms significantly affected the plasma concentrations of quetiapine versus risperidone, especially at week 6 after monotherapy. This suggests that when taking quetiapine or risperidone as a monoadministration, patients need to be regularly monitored for changes in plasma concentrations, especially in the sixth week of treatment, in order to prevent the occurrence of toxicity due to high plasma concentrations in carriers of the TT phenotype at the rs10042486 locus and the GG phenotype at the rs6295 locus, or plasma concentrations lower than the therapeutic reference concentration range occurring in carriers of the CC phenotype at the rs10042486 locus and the CC genotype at the rs6295 locus.…”
Section: Discussionsupporting
confidence: 47%